Intergroup Contact and Exposure to Information about Immigrants: Experimental Evidence - Patrick Dylong; Silke Uebelmesser (Center for Economic Studies and ifo Institute (CESifo), 2023)
We examine the relationship between beliefs about and attitudes towards immigrants and intergroup contact between natives and migrants in eastern Germany, a region characterized by anti-immigrant sentiment. Using probability-based survey data, we randomly vary respondents' access to a signal about the true size of the immigrant population in the region. Respondents who receive the signal show more supportive attitudes toward immigration, with effect sizes being more pronounced for attitudes toward high-skilled immigrants. Importantly, estimating conditional average treatment effects shows that respondents who have less contact with immigrants prior to our intervention respond more strongly to the treatment. Additional findings suggest that the level of intergroup contact and biased beliefs about immigrants are complementary targets for information campaigns on immigration.
Keywords: C90; D83; F22; J15; 330; beliefs about immigrants; immigration attitudes; intergroup contact; information campaign